1990
DOI: 10.1111/j.1365-2125.1990.tb03847.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of cimetidine as a selective inhibitor of dapsone N‐ hydroxylation in man.

Abstract: 1 The N-hydroxylation of dapsone is thought to be responsible for the methaemoglobinaemia and haemolysis associated with this drug. We wished to investigate the effect of concurrent administration of cimetidine (400 mg three times per day) on the disposition of a single dose (100 mg) of dapsone in seven healthy volunteers in order to inhibit selectively N-hydroxylation.2 The AUC of dapsone (31.0 ± 7.2 ,ug ml-' h) was significantly increased (P < 0.001) in the presence of cimetidine (43.3 ± 8.8 ,ug ml-' h).3 Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 23 publications
6
35
0
Order By: Relevance
“…This metabolite is formed due to the N-hydroxylation of dapsone by multiple hepatic cytochrome P450 isozymes, including CYP3A4 [23][24][25][26] . Cimetidine, a histamine H 2 receptor antagonist, can reduce the N-hydroxylation of dapsone [31] . This reduction was demonstrated to result in more than a 25% decrease in methemoglobinemia in patients who received dapsone for the treatment of dermatitis herpetiformis [32] .…”
Section: Discussionmentioning
confidence: 99%
“…This metabolite is formed due to the N-hydroxylation of dapsone by multiple hepatic cytochrome P450 isozymes, including CYP3A4 [23][24][25][26] . Cimetidine, a histamine H 2 receptor antagonist, can reduce the N-hydroxylation of dapsone [31] . This reduction was demonstrated to result in more than a 25% decrease in methemoglobinemia in patients who received dapsone for the treatment of dermatitis herpetiformis [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Since losartan has been shown to be extensively metabolized in human liver slice incubations [22], the most likely explanation for the decrease in losartan AUC is inhibition of one or more cytochrome P450 pathways for metabolism of losartan, (presumably CYPs 3A4 and 2C9 [6]). Cimetidine has been shown to alter the metabolism of other drugs which are metabolized by CYP 3A4, including dihydropyridine calcium channel blockers [7,8,9], dapsone [10], and midazolam [7]. Other mechanisms may apply including inhibition of renal tubular secretion of losartan, although the minor role of the renal route in the elimination of losartan (only 3% of an oral dose of losartan is excreted unchanged in the urine in patients with normal renal function [23]) suggests that this is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…While losartan is not a prodrug, formation of the metabolite is important to the activity of losartan as a once-daily treatment of hypertension [5]. Available in vitro data suggest that this reaction can be catalysed by CYPs 3A4 and 2C9 [6].Numerous studies have shown that cimetidine, a commonly prescribed H2-antagonist, nonspecifically inhibits the oxidative metabolism of many drugs, including those metabolized by CYP 3A4 such as nifedipine, nisoldipine and dapsone [7][8][9][10]. Since the duration of action of losartan is dependent on the formation of E-3174, it was of interest to determine whether cimetidine alters concentrations in plasma of losartan and/or E-3174.…”
mentioning
confidence: 99%
“…Unfortunately the applications of dapsone are dose-limited due to its hepatic phase I activation to haemotologically toxic hydroxylamines [12,13].…”
Section: -Aminodiphenyl Sulphones and Especially 44mentioning
confidence: 99%